Rheological Characterization of Starch Nanoparticles from Different Botanical Sources - VIKASH NAIN; KAWALJIT SINGH SANDHU (International Journal of Pharma and Bio Sciences, 2018)
The rheological behavior of starch nanoparticles from different botanical sources was investigated to study the effect of various parameter like frequency, stress, temperature etc. Suspensions containing 10% (w/w) starch nanoparticles (SNPs) from various sources (wheat, mung bean, potato, water chestnut and mango kernel) were prepared The continuous shear viscosity test, pasting, flow behavior test, the frequency sweep (FS) and creep-recovery (CR) test were carried out. The suspensions having water chestnut nanoparticles exhibited highest apparent viscosity within shear rate (SR) range (0.1–100 s−1) and temperature range (50-95°C). The suspensions having potato and water chestnut nanoparticles showed shear thinning and thixotropic behavior in comparison to others which exhibited shear thickening behavior. In addition, the suspensions containing mango kernel SNPs showed highest deformation recovery capacity in creep recovery measurements. Potato SNPs suspension had highest storage modulus (SM) (GêžŒ), loss modulus (LM) (GêžŒêžŒ) and complex viscosity (η*) during frequency sweep measurement at 6.28 rad/s. The rheological behavior of starch nanoparticles provide useful information for their usage in food as well as industrial applications. Comparison of starch nanoparticles from different botanical sources also revealed suitability of particular nanoparticle suspension for desired application in food system.